Towards a plan of actions for mankind, v.4 : designs of global systems models and their limitations - Marois, M.; Institut de la vie. (London : New York : Pergamon Press, 1977)
Articles prepared for the world conference sponsored by the Institut de la vie.
English or French.
Proceedings of the world conference sponsored by Institut de la vie and held in Paris, Sept. 9-13, 1974.
Includes bibliographical references.
lje 24/01/2018
Loans
Keywords: Human ecology; Environmental policy---Mathematical models; Economic development; System analysis---Mathematical models